Evaluation of a national surveillance unit. Issue 1 (1st January 1999) - Gazarian, Madlen; Williams, Katrina; Elliott, Elizabeth; Chant, Kerry; Longbottom, Helen; Mellis, Craig; Nolan, Terry; Oates, R K; Ruben, Alan
Abstract : AIM: The Australian Paediatric Surveillance Unit (APSU) facilitates national active surveillance of uncommon childhood conditions. This study assessed whether it fulfilled its objectives and satisfied criteria established by the Centers for Disease Control and Prevention (CDC) for evaluating surveillance systems. METHODS: Anonymous questionnaires were sent to users of the system, individual studies were reviewed, and data were collected from independent sources. RESULTS: Seven hundred and sixty six clinicians, 48 investigators, and 15 public health professionals responded to the questionnaires. Clinicians reported that the APSU was useful, 33% saying information provided by the APSU informed or changed their clinical practice. Most (88%) reported that completing monthly report cards was not a burden. Impact on policy development was limited by suboptimal dissemination of information to public health professionals. Flexibility and timeliness were limited by design. Estimated sensitivity of APSU studies ranged from 92% (congenital rubella) to 31% (drowning/near drowning). Positive predictive value of notified cases was over 70% for most studies. CONCLUSION: The APSU fulfils most of its objectives and meets CDC criteria salient to these. Ways in which the APSU could be improved have been identified, as have methodological challenges and limitations in applying CDC guidelines to this type of unit.